A Study on Assessment of Risk of Type 2 Diabetes Mellitus among Bank Employees Using Indian Diabetic Risk Score - Vidya GS; Sandesh TR; Navneet Kaur (Medsci Publications, 2016)
Background: With the changing life style in the recent decade risk of chronic non-communicable diseases like diabetes mellitus has increased globally. The present study was conducted to assess the bank employees for risk factors of type 2 Diabetes mellitus using Indian Diabetic Risk Score (IDRS). Methods: A cross sectional field based study was carried out over a period of 2 months(June-July 2015) among employees of 8 branches of Bapuji Co-operative bank spread over the city of Davangere, Karnataka.Total 90 employees were available for the study. Data was collected by using a Pre tested and pre designed proforma, Indian Diabetic Risk Score(IDRS) and body measurements were taken. Results: Out of 90 subjects, 71(78.8%) were males & 19(21.1%) were females. Age of subjects ranged from 25-55yrs. According to IDRS, 15(16.6%) were in high risk group, 55(61.1%) of them were in moderate risk group and 20(22.2%) were in low risk group for type 2 DM. Conclusion: In our study 16.6% of the bank employees were at high risk of type 2 DM and 61% were at moderate risk of developing type 2 DM.